Stirring the pot: Switching from blended fee‐for‐service to blended capitation models of physician remuneration. (19th August 2020) - Somé, Nibene H.; Devlin, Rose Anne; Mehta, Nirav; Zaric, Gregory S.; Sarma, Sisira
Abstract: In Canada's most populous province, Ontario, family physicians may choose between the blended fee‐for‐service (Family Health Group [FHG]) and blended capitation (Family Health Organization [FHO] payment models). Both models incentivize physicians to provide after‐hours (AH) and comprehensive care, but FHO physicians receive a capitation payment per enrolled patient adjusted for age and sex, plus a reduced fee‐for‐service while FHG physicians are paid by fee‐for‐service. We develop a theoretical model of physician labor supply with multitasking to predict their behavior under FHG and FHO, and estimable equations are derived to test the predictions empirically. Using health administrative data from 2006 to 2014 and a two‐stage estimation strategy, we study the impact of switching from FHG to FHO on the production of a capitated basket of services, after‐hours services and nonincentivized services. Our results reveal that switching from the FHG to FHO reduces the production of capitated services to enrolled patients and services to nonenrolled patients by 15% and 5% per annum and increases the production of after‐hours and nonincentivized services by 8% and 15% per annum.